The Writer's Way in France - Cohn, Robert Greer (University of Pennsylvania Press, 2016)
Acknowledging his debts to numerous post-Hegelian philosophers or psychologists and modern critics, Robert Greer Cohn offers a lucid and swift-paced account of an original view of literature that bears particular kinship to the artistic visions of Joyce, Mallarmé, and Proust.